Platelet-derived PF4 reduces neutrophil apoptosis following arterial occlusion - Hartwig, Helene; Drechsler, Maik; Lievens, Dirk; Kramp, Birgit; Hundelshausen, Philipp von; Lutgens, Esther; Weber, Christian; Döring, Yvonne; Soehnlein, Oliver (Thrombosis and Haemostasis, 2014)
Note: The editorial process for this manuscript was fully handled by Gregory Y. H. Lip, Editor in Chief.